THE USE OF CODE-MIXING IN INSTAGRAM CAPTIONS FROM THE STUDENTS OF ENGLISH LITERATURE STUDY PROGRAM, UNIVERSITAS RESPATI YOGYAKARTA: A SOCIOLINGUISTIC STUDY - Ismia Fa'da; Tri Septa Nurhantoro; Yohanes Angie Kristiawan (Universitas Respati Yogyakarta (UNRIYO), 2023)
This research discusses the code mixing used in the Instagram caption by students English Literature Study Program at Universitas Respati Yogyakarta. This research aims to find the types of code mixing used in Instagram captions and to understand the factors using code mixing in captions. The focus analysis of this research is by analyzing the context. This research was conducted by implementing a descriptive qualitative method in discussing code-mixing. A simple quantitative method is implemented to assist the qualitative method in explaining the data in the form of numbers or percentages. The findings of this research show that there are 70 code-mixing data found in Instagram captions. The analysis findings show that there are three types of code mixing found in Instagram captions. Those are code-mixing insertion, alternation and congruent lexicalization. From the results of the analysis in this research, the type of insertion is the type that is the highest or most commonly found, that is 54 data (59.1%). Then alternation type with 12 data (17.1%), and congruent lexicalization type with 4 data (5.71%). and for the results of the second question in this research, there are 60 data (85.71%) for the first factor talking about a particular topic, the second factor is being emphatic about something with 4 data (5.71%), the third factor is repetition used for clarification with 4 data (5.71%) and 2 data (4, 28) for the expressing group identity.